Analisis Dampak Islamicity Performance Index dan Modal Intelektual terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia - Ruri Rahmaniar; Ruhadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to determine the extent to which Islamic banks in Indonesia apply sharia principles in carrying out their operational activities, by looking at the impact of the Islamicity lPerformance lIndex lindicators, namely lProfit lSharing lRatio, lZakat lPerformance lRatio, Equitable lDistribution Ratio, Directors-Employees Welfare Ratio, Islamic Income vs Non-Islamic lIncome, land lalso lintellectual lcapital on the financial performance of Islamic Banks by using the profitability ratio as a measure of bank performance. Secondary data were obtained from financial reports published by Islamic Banks in Indonesia for the period 2010-2018. The results indicate that the Zakat Performance Ratio partially had a significant positive impact on ROA, the Equitable Distribution Ratio and intellectual capital have a partially significant negative impact on ROA, besides simultaneously the profit sharing ratio, zakat performance ratio, equitable distribution ratio, directors-employees welfare ratio, Islamic income vs non-Islamic income, and intellectual capital have a significant impact on ROA.